Swedish - Finnish glossary: meeting and session words - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary containing meeting and session words. Published in Kieliviesti 1/2008. Contains approximately 120 entries. 2008.

Svensk-sverigefinsk ordlista med mötes- och sammanträdesord. Publicerades i Kieliviesti 1/2008. Innehåller ca 120 ord. 2008.
Svensk-finsk ordlista: mötes- och sammanträdesord
Keywords: meetings; möten; governing boards (organizations); styrelser (organisationer); decision process; beslutsprocess; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur